The subject supposed to vote - Godley, J. Asher (Filozofski vestnik, 2025)
In chapter 6 of Read My Desire, Joan Copjec argues that the constitutive limits of American democracy reveal themselves symptomatically in the electoral choice of a conspicuously incompetent sovereign figure. In a leader for whom governing is exposed as an “impossible profession” (Freud), the Other’s castration appears as a universal sign, which provokes an hysterical form of love even among would-be critics. This essay examines a crucial supplementation to this leader-group dynamic in the “neighborly” structure of voting. When a subject votes, she registers a signifier of her difference as a mark that both estranges her (by turning her difference into a data point) and also situ-ates her in an equivalent alignment with other voters who are either “with” or “against” her position, enabling an imaginary mirror play. From this position of non-interaction and reflective doubling, the subject is invited to participate in a peculiar calculation with respect to what are known as “swing voters,” a demographically constructed set of individuals whose presumptive action is thought to decide the nation’s fate. This hypo-thetical “subject supposed to vote” is then considered such that the voter, as well as the candidate, adjust their actions based on the anticipated certainty of the fateful mark. In the election cycles that have come to dominate virtually every aspect of civic life, the imputed calculations of this little semblable (granted informational density through interminable polling and fantasized in racist caricature) exert a temporal pressure on democratic subjects that often forces hasty decisions. Through a comparative reading of Copjec’s chapter with Lacan’s essay “Logical Time,” this essay concludes by interpret-ing the intersubjective logic behind this temporal forcing.
Keywords: democracy; demokracija; election; psihoanaliza; psychoanalysis; sovereignty; suverenost; Trump, Donald; volitve